Кримінологія та синергетика: деякі методологічні аспекти - Денисов, С. Ф.; Denysov, S. F.; ORCID: https://orcid.org/0000-0002-1218-0016; Тимчук, О. Л.; Tymchuk, O. L. (Українська поліцеїстика: теорія, законодавство, практика. - 2021. - № 2(2). - С. 9-18, 2021)
Проаналізовано методологічні аспекти використання синергетики в кримінології. Охарактеризовано сутність синергетичної парадигми в природничих і соціальних науках, наведено основні підходи вчених щодо перспектив і напрямів застосування синергетичних ідей та понять для вирішення ключових проблем кримінології. Критично оцінено погляди деяких науковців на синергетику як універсальний метод, застосування якого дозволить по-новому вирішити традиційні кримінологічні питання.

The article analyzes the methodological aspects of the use of synergetics in criminology. The essence of the synergetic paradigm in natural and social sciences is characterized, the main approaches of scientists regarding the prospects and directions of application of synergetic ideas and concepts for solving key problems of criminology are given. Predominantly synergetics is considered as the science of self-organization and self-organizing systems, the theory of evolution of open-type systems with nonlinear feedbacks. The focus of synergetics is on the processes of selforganization in complex systems. From the use of synergetics in the social sciences (including criminology), its proponents expect significant positive effects in the form of new scientific theories. Over the past 20 years, synergetic ideas have gained significant popularity in Ukrainian criminology, however, until now, it is mainly about posing the problem in general terms, stating the importance / timeliness / prospects of using synergetics to solve traditional criminological issues, for example, the determination of crime, the mechanism of criminal behavior, study of organized crime, crime prevention. In some cases, criminological concepts and problems are artificially “adjusted” to synergistic categories. The views of some scientists on synergetics as the only or universal method, the application of which will allow to solve all traditional criminological issues in a new way, are critically assessed. It is emphasized that there are few concrete examples of the actual application of synergetics in criminological research, allowing us to see its real advantages over other “traditional” methods. At the same time, synergetics has prospects, since over time, as other social sciences (primarily sociology) develop, provided that synergetic ideas are effectively used in them, this method will be able to find its application in the field of criminology.

Проанализированы методологические аспекты использования синергетики в криминологии. Охарактеризована сущность синергетической парадигмы в естественных и социальных науках, приведены основные подходы ученых к перспективам и направлениям применения синергетических идей и понятий для решения ключевых проблем криминологии. Критически оценены взгляды некоторых ученых на синергетику как универсальный метод, применение которого позволит по-новому решить традиционные криминологические вопросы.
Criminology and synergetics: some methodological aspects
Денисов, С. Ф. Кримінологія та синергетика: деякі методологічні аспекти / Денисов Сергій Федорович, Тимчук Олексій Леонідович // Українська поліцеїстика: теорія, законодавство, практика. - 2021. - № 2(2). - С. 9-18. - DOI: https://doi.org/10.32366/2709-9261-2021-2-2-9-18.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; синергетика; synergy; методологія; methodology; методология; погляди вчених; views of scientists; взгляды ученых; кримінологічна наука; criminological science; криминологическая наука